The effectiveness of clear aligners in levelling the curve of Spee and related maxillofacial factors in patients with a deep overbite - Zhang Li; Gong Beiwen; Xie Xianju; Cao Li; Gu Yingzhi; Sun Yaxi; Bai Yuxing (Sciendo, 2024)
To guide deep overbite treatment, the effectiveness of clear aligners and the influence of maxillofacial characteristics were assessed in levelling the curve of Spee (COS).